Readiness for interprofessional learning: a cross-faculty comparison between architecture and occupational therapy students. Issue 5 (13th May 2013) - Larkin, Helen; Hitch, Danielle; Watchorn, Valerie; Ang, Susan; Stagnitti, Karen
Abstract: Health and wellbeing includes a need for built environments to accommodate and be inclusive of the broadest range of people and a corresponding need to ensure graduates are ready to engage in this field of interprofessional and inter-industry practise. All too often, interprofessional education in higher education is neglected with a tendency towards educational silos, particularly at a cross-faculty level. This paper reports on an initiative that embedded universal design practice education into the curricula of first year architecture and third year occupational therapy students and evaluated the impact on students' readiness for interprofessional learning. The Readiness for Interprofessional Learning Scale (RIPLS) was given to students at the beginning and end of the semester during which students participated in a variety of online and face-to-face curriculum initiatives. Results showed that at the beginning of semester, occupational therapy students were significantly more positive about interprofessional learning than their architecture counterparts. Post-results showed that this trend continued but that occupational therapy students became less positive on some items after the interprofessional learning experience. This study provides insights into the interprofessional learning experiences of a group of students who have not previously been studied within the available literature.